Focused Ultrasound and RadioTHERapy for non-invasive palliative pain treatment in patients with bone metastasis: a study protocol for the three armed randomized controlled FURTHER trial - Slotman Derk J; Bartels Marcia MTJ; Ferrer Cyril J; Bos Clemens; Bartels Lambertus W.; Boomsma Martijn F.; Phernambucq Erik C. J.; Nijholt Ingrid M.; Morganti Alessio G.; Siepe Giambattista; Buwenge Milly; Grüll Holger; et al. (BMC, 2025)
Background
Cancer-induced bone pain (CIBP), caused by bone metastases, is a common complication of cancer and strongly impairs quality of life (QoL). External beam radiotherapy (EBRT) is the current standard of care for treatment of CIBP. However, approximately 45% of patients have no adequate pain response after EBRT. Magnetic resonance image-guided high-intensity focused ultrasound (MR-HIFU) may improve pain palliation in this patient population. The main objective of this trial was to compare MR-HIFU, EBRT, and MR-HIFU + EBRT for the palliative treatment of bone metastases.
Methods/design
The FURTHER trial is an international multicenter, three-armed randomized controlled trial. A total of 216 patients with painful bone metastases will be randomized in a 1:1:1 ratio to receive EBRT only, MR-HIFU only, or combined treatment with EBRT followed by MR-HIFU. During a follow-up period of 6 months, patients will be contacted at eight time points to retrieve information about their level of pain, QoL, and the occurrence of (serious) adverse events. The primary outcome of the trial is pain response at 14 days after start of treatment. Secondary outcomes include pain response at 14 days after trial enrolment, pain scores (daily until the 21st day and at 4, 6, 12 and 24 weeks), toxicity, adverse events, QoL, and survival. Cost-effectiveness and cost-utility analysis will be conducted.
Discussion
The FURTHER trial aims to evaluate the effectiveness and cost-effectiveness of MR-HIFU—alone or in combination with EBRT—compared to EBRT to relieve CIBP. The trial will be performed in six hospitals in four European countries, all of which are partners in the FURTHER consortium.
Trial registration
The FURTHER trial is registered under the Netherlands Trials Register number NL71303.041.19 and ClinicalTrials.gov registration number NCT04307914. Date of trial registration is 13–01-2020.